# Find the derivative of x.cosx by using the formulas of the derivatives.

2
by Raksha1

2015-10-31T17:35:52+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Use the formula, d/dx(u*v) = u* d/dx(v) + v* d/dx(u)

d/dx(x*cosx)
= x* d/dx(cosx) + cosx* d/dx(x)
= x*(-sinx) + cosx * 1
= -x.sinx + cosx
Thanks Raksha!
Deeksha!!
2015-10-31T18:09:50+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Okay.... !! Let , y = xcosx ------(1) Using product rule , d/dx[f(x).g(x)] = f(x).d/dx{g(x)} + g(x).d/dx{f(x)} Differentiating equation 1 w.r.t. 'x' dy/dx = x(-sinx) + cosx dy/dx = cosx - xsinx